KEJADIAN LUAR BIASA POLIOMIELITIS DI INDONESIA PADA TAHUN 2022-2023: SUATU TINJAUAN - Meiriani Sari; Firda Fairuza; Nia Nurul Aziza; Dita Setiati (Fakultas Kedokteran Universitas Trisakti, 2024)
Indonesia achieved polio eradication along with several other members of the Southeast Asia Regional Organization (SEARO) in 2014 because it succeeded in overcoming the disease caused by the wild polio virus. Unfortunately since then Indonesia has experienced several reported outbreaks. This literature review aims to analyze the factors causing the re-emergence of poliomyelitis in Indonesia after being declared polio-free in 2014 and effective steps to stop outbreaks and prevent the re-emergence of poliomyelitis. Awareness of health workers and the public regarding polio must be increased so that Indonesia and the world can soon be polio-free. The last two outbreaks occurred in Indonesia in 2022 and 2023. The first outbreak in 2022 was in Pidie Regency, Aceh, Indonesia. In response to the poliomyelitis outbreak, the government immediately launched a simultaneous vaccination program. Since then no cases of poliomyelitis have been found until another case was found in December 2023 in Solo, Central Java, Indonesia. Once again, to respond to the poliomyelitis outbreak, the government held a simultaneous vaccination program in three districts, namely Pamekasan and Sampang, East Java and Klaten, Central Java. Followed after that by all regions in Central Java and East Java. It is expected that this quick response from the government can stop the outbreak again. The target of SubPIN (National Immunization Subweek) is to break the chain of transmission, so it must ensure that Outbreaks Response Immunization (ORI) coverage is high at least 95% and evenly distributed throughout the region. Apart from that, information to the public regarding the dangers of disease and the importance of complete vaccination to prevent disease must continue to be provided.